Research advances of the establishment and characterization of Helicobacter pylori infection animal models - Zhang, Kaifang; Cui, Man; Zhu, Yuefeng; Li, Songping; Su, Guimin; Du, Lin (Frontiers in Microbiology, 2025)
Helicobacter pylori (Hp) is a major pathogenic bacterium responsible for gastritis, peptic ulcers, and gastric cancer. The prevention and control of Hp infection pose significant global health challenges, particularly due to the rising antibiotic resistance alongside the current absence of an effective vaccine. This review synthesizes the key elements governing successful model establishment, including strain characteristics, animal host species selection, pre-treatment methods, and infection protocols. It further elaborates on the methods for detecting and quantifying Hp in animal models, including invasive and non-invasive detection techniques for model validation, and explores the potential applications of spatial transcriptomics in this field. Furthermore, the review outlines current progress and limitations in Hp infection modeling. Aimed at supporting preclinical research, this review serves as a practical reference for establishing stable and reproducible animal models that mimic human infection and disease progression, thereby facilitating the evaluation of novel therapeutics and vaccine candidates.